2014
DOI: 10.1002/marc.201400414
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Self‐Assembly of PDMA‐b‐PS Chains into Granular Nanoparticles: Genesis and Fate

Abstract: The hierarchical self-assembly of an amphiphilic block copolymer, poly(N,N-dimethylacrylamide)-block-polystyrene with a very short hydrophilic block (PDMA10 -b-PS62 ), in large granular nanoparticles is reported. While these nanoparticles are stable in water, their disaggregation can be induced either mechanically (i.e., by applying a force via the tip of the cantilever of an atomic force microscope (AFM)) or by partial hydrolysis of the acrylamide groups. AFM force spectroscopy images show the rupture of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The high molar relaxivity values show high promise for application as an MRI agent, since both the r 1 and r 2 values are comparable to top end commercial contrast agents [ 38 ]. In addition, the inclusion of PTX did not significantly influence the relaxometric parameters, suggesting theranostic applications.…”
Section: Resultsmentioning
confidence: 99%
“…The high molar relaxivity values show high promise for application as an MRI agent, since both the r 1 and r 2 values are comparable to top end commercial contrast agents [ 38 ]. In addition, the inclusion of PTX did not significantly influence the relaxometric parameters, suggesting theranostic applications.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical characterization on single‐particle scale can be of strategic interest in order to gather a deeper insight on the inner morphology of the nanostructure. Particularly, AFM force‐versus‐distances curves, so‐called force spectroscopy measurements, can be used to characterize the mechanical properties of polymer vesiscles and polymer granular nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…In particular, some of the authors have shown recently that polymers having a large prevalence of PDMA (PDMA 817 ‐ b ‐PS 105 ) in water form large core–corona micelles with hydrodynamic diameter of 125nm, where shorter, insoluble PS block forms a small spherical core on which the longer, soluble PDMA chains are tethered to form a large solvated corona . Instead, shorter block copolymers with large prevalence of PS (PDMA 10 ‐ b ‐PS 62 ) give rise to large granular objects with hydrodynamic diameters in the order of 200–300 nm . Both of these systems are expected to be too big to cross the BBB, thus a PDMA/PS ratio of about 1/3 was targeted.…”
Section: Resultsmentioning
confidence: 99%
“…By using selective solvents, temperature or other stimuli it is then possible to control the self‐assembly of ABC and obtain a plethora of nanostructures ranging from spherical and worm‐like micelles to vesicles . Poly( N , N ‐dimethylacrylamide)‐ b ‐polystyrene (PDMA‐ b ‐PS) is one of those polymers, that already demonstrated the capability to form core–corona NP and hierarchical granular NP …”
Section: Introductionmentioning
confidence: 99%